Advancements in the Management of Follicular Lymphoma: A Comprehensive Review - Reid Merryman; Özgür Mehtap; Ann Lacasce (Turkish Journal of Hematology, 2024)
Follicular lymphoma (FL) is the most common subtype of indolent non-Hodgkin lymphoma in Western countries. While FL is generally incurable, standard initial therapies are associated with high response rates and durable remissions for most patients. In addition, novel targeted agents and immunotherapies are changing the treatment algorithm for patients with relapsed or refractory disease. This review discusses the initial staging, prognosis, and treatment options for newly diagnosed and relapsed/refractory FL. Initial treatment options for FL include active surveillance, radiotherapy, rituximab monotherapy, and chemoimmunotherapy. Staging with positron emission tomography/ computed tomography and bone marrow biopsy is crucial for identifying early-stage patients. Most patients with FL will receive chemoimmunotherapy as the initial treatment with options including rituximab or obinutuzumab plus cyclophosphamide, vincristine, and prednisone; cyclophosphamide, doxorubicin, vincristine, and prednisone; bendamustine; or lenalidomide. No significant differences in overall survival have been observed in randomized studies comparing these regimens. Maintenance therapy with rituximab or obinutuzumab in responders to initial chemoimmunotherapy improves progression-free survival. For relapsed/refractory FL, treatment options include chemoimmunotherapy, lenalidomidebased regimens, tazemetostat, chimeric antigen receptor (CAR)-T cell therapy (axicabtagene ciloleucel and tisagenlecleucel), and CD3/ CD20 bispecific antibodies (BsAbs). Given the encouraging outcomes obtained with CAR-T cell therapy and BsAbs, multiple trials are testing these highly active agents in earlier lines of therapy and among highrisk patients with early relapse after frontline chemoimmunotherapy. Additional studies and follow-up are needed to understand how these novel agents may further change treatment algorithms for FL.